Pengaruh Brand Ambassador Red Velvet pada Azarine Cosmetic terhadap Brand Image dan Minat Pembelian yang Memiliki Dampak pada Keputusan Pembelian Penggemar K-Pop (ReVeluv) di Indonesia - Agueni, R. Pahlevi Dwirezki; Suyanto, Achmad Manshur Ali (Universitas Batanghari Jambi, 2024)
During the Covid-19 pandemic, businesses had to close, but this differs from the beauty and cosmetics industry. This was shown by the increasing number of companies in the industry from 2021 to 2022. With the increasing number of local beauty and cosmetics companies, brands need the right marketing strategy, namely, using a brand ambassador strategy. Azarine implemented this strategy with Red Velvet. The selection of Red Velvet by Azarine was carried out, taking advantage of the increasing Korean Wave in Indonesia. This study aims to determine the influence of Red Velvet's brand ambassador on Azarine Cosmetics on brand image and purchase intention, which impacts purchasing decisions of K-Pop fans (ReVeluv) in Indonesia. The research process was carried out using a quantitative method through questionnaires to 385 female respondents, Red Velvet fans aged 18-40 years, and domiciled in DKI Jakarta, West Java, Central Java, East Java, and Banten. The analysis process of this study is to use SPSS and also AMOS. This study produces the results of the hypothesis that Red Velvet has a positive and significant influence on Azarine's brand image, Red Velvet has a positive and significant effect on Azarine's purchase intention, Azarine’s brand image has an effect on the purchasing decisions of Red Velvet fans, and Azarine's buying interest has an influence on the purchasing decisions of Red Velvet fans. Not only that, the results of the study show that Red Velvet as Azarine's brand ambassador has a more optimal influence on purchasing decisions for K-Pop fans (ReVeluv) by increasing Azarine's brand image, compared to through purchase intention that appears on K-Pop fans ( ReVeluv).